Static stretching can impair explosive performance for at least 24 hours - Haddad, M.; Dridi, A.; Chtara, M.; Chaouachi, A.; Wong, D. P.; Behm, D.; Chamari, K. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to compare the effects of static vs. dynamic stretching (DS) on explosive performances and repeated sprint ability (RSA) after a 24-hour delay. Sixteen young male soccer players performed 15 minutes of static stretching (SS), DS, or a no-stretch control condition (CC) 24 hours before performing explosive performances and RSA tests. This was a within-subject repeated measures study with SS, DS, and CC being counterbalanced. Stretching protocols included 2 sets of 7 minutes 30 seconds (2 repetitions of 30 seconds with a 15-second passive recovery) for 5 muscle groups (quadriceps, hamstring, calves, adductors, and hip flexors). Twenty-four hours later (without any kind of stretching in warm-up), the players were tested for the 30-m sprint test (with 10- and 20-m lap times), 5 jump test (5JT), and RSA test. Significant differences were observed between CC, SS, and DS with 5JT (F = 9.99, p < 0.00, effect size [ES] = 0.40), 10-m sprint time (F = 46.52, p < 0.00, ES = 0.76), 20-m sprint time (F = 18.44, p < 0.000, ES = 0.55), and 30-m sprint time (F = 34.25, p < 0.000, ES = 0.70). The significantly better performance (p < 0.05) was observed after DS as compared with that after CC and SS in 5JT, and sprint times for 10, 20, and 30 m. In contrast, significantly worse performance (p < 0.05) was observed after SS as compared with that after CC in 5JT, and sprint times for 10, 20, and 30 m. With RSA, no significant difference was observed between different stretching protocols in the total time (F = 1.55, p > 0.05), average time (F = 1.53, p > 0.05), and fastest time (F = 2.30, p > 0.05), except for the decline index (F = 3.54, p < 0.04, ES = 0.19). Therefore, the SS of the lower limbs and hip muscles had a negative effect on explosive performances up to 24 hours poststretching with no major effects on the RSA. Conversely, the DS of the same muscle groups are highly recommended 24 hours before performing sprint and long-jump performances. In conclusion, the positive effects of DS on explosive performances seem to persist for 24 hours.